Redefining Legal Frameworks: Progressive Methods in Ascertaining Children's Lineage from Fasid Marriages in Religious Court Proceedings - Fitriyadi, Fitriyadi; Hidayati, Tri; Hasan, Ahmadi; Sarmadi, Akhmad Sukris (Universitas Islam Negeri Antasari Banjarmasin, 2024)
This research aims to reveal and analyze the considerations of the panel of judges in cases of determining the origin of children because the marriage was annulled (fasid) in all Religious Courts in South Kalimantan, and offers an ideal legal construction in determining the origin of children in the context of legal protection for children based on a legal approach progressive. This research is normative legal research, using case, statutory, and concept approaches. The analysis process uses content analysis techniques. The results determine the origin of children from fasid marriages at the Religious Courts in South Kalimantan from 2020 to 2022 consisting of 13 who rejected the request and 15 who granted the request. Those who agreed considered the importance of child protection based on the Child Protection Law and the Opinions of Contemporary Ulama. On the other hand, those who reject it based on the Marriage Law and KHI that fasid marriages are materially and formally invalid so that their children become illegitimate. Protection for children is a fundamental right that judges must explore with a progressive legal approach, that children from fasid marriages must not bear the burden of their parent's mistakes and negligence on legal rules.